Killer cell immunoglobulin‐like receptor three domains long cytoplasmic tail 1 gene *007 may modulate disease progression of human immunodeficiency virus‐1 infection in the Japanese population. (17th February 2023) - Naruse, Taeko K.; Konishi‐Takemura, Makiko; Yanagida, Risa; Sharma, Gaurav; Vajpayee, Madhu; Terunuma, Hiroshi; Mehra, Narinder K.; Kaur, Gurvinder; Kimura, Akinori
Abstract: One of the KIR allele, KIR3DL1*007, was associated with the progression to acquired immunodeficiency syndrome and not with the susceptibility to HIV‐1 infection in the Japanese and Indian populations, implying that KIR3DL1*007 ‐positive NK cells might eliminate HIV‐infected cells less effectively than NK cells bearing the other KIR3DL1 alleles or KIR3DS1 alleles.